The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3233/nha-200108
|View full text |Cite
|
Sign up to set email alerts
|

Cleistocalyx nervosum var. paniala seed extracts exhibit sigma-1 antagonist sensitive neuroprotective effects in PC12 cells and protect C. elegans from stress via the SKN-1/NRF-2 pathway

Abstract: BACKGROUND: Cleistocalyx nervosum var. paniala (C. nervosum) is a plant that produces berries that are popular as a health food in Thailand. In previous studies we have identified C. nervosum fruit extracts to have anti-aging and anti-stress properties in C.elegans OBJECTIVE: Evaluate the neuroprotective properties of C. nervosum seed extracts and investigate the mechanisms behind their neuroprotective properties. METHODS: PC-12 cells were differentiated using NGF and treated with amyloid-β (Aβ)  (25–35)  crea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 86 publications
0
6
0
Order By: Relevance
“…The obtained images were processed using Image J and fluorescence intensity was denoted in arbitrary units (AU) [13].…”
Section: Fluorescence Imagingmentioning
confidence: 99%
See 1 more Smart Citation
“…The obtained images were processed using Image J and fluorescence intensity was denoted in arbitrary units (AU) [13].…”
Section: Fluorescence Imagingmentioning
confidence: 99%
“…C. elegans have been used to study the antiaging, stress resistance and neuroprotective effects of various traditional medicinal plants including, Cleistocalyx nervosum [13,14], Lignosus rhinoceros [15], Bacopa monnieri [16], Caesalpinia mimosoides [17] and Diplocyclos palmatus [18]. In the present study, the anti-aging and neuroprotective effects of KP and its active constituent DMF has been analyzed using C. elegans model.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies with herbal extracts have identified increased neurite outgrowth 10 as a potential feature of the herb's neuroprotective properties. 11,12 Thai medicinal herb Streblus asper Lour. (SA) Has previously been shown to protect against photoaging and provide neuroprotection in C.elegans.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, the pulp extract of CN also exerted an anti-aging effect by increasing the life span of Caenorhabditis elegans model and neuroprotective effects in glutamate-induced oxidative stress in mouse hippocampal cell line (HT-22) ( Nantacharoen et al., 2022 ; Prasanth et al., 2019 ; Sukprasansap et al., 2017 ). However, the seed of this fruit, which is classified as a waste by-product of agricultural food production has not yet been investigated for its medicinal properties, despite its neuroprotective effects having been demonstrated ( Brimson et al., 2021 ). Furthermore, resveratrol (RESV), a natural compound found in several berry fruits, is regarded as the NF-κB signaling inhibitor ( Kadri et al., 2019 ; Ma et al., 2015 ; Pap et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%